Clinical Expertise Is Core to an Evidence-Based Approach to Auditory Processing Disorder: A Reply to Neijenhuis et al. 2019 - Iliadou, Vasiliki; Kiese-Himmel, Christiane; Bamiou, Doris-Eva; Grech, Helen; Ptok, Martin; Chermak, Gail D.; Thai-Van, Hung; Stokkereit Mattsson, Tone; Musiek, Frank E. (Frontiers in Neurology, 2019)
The opinion article “An Evidence-based Perspective on Misconceptions Regarding Pediatric Auditory Processing Disorder” by Neijenhuis et al. (1) presents a distorted view of the evidence-based approach used in medicine. The authors focus on the amorphous non-diagnostic entity “listening difficulties” not auditory processing disorder (APD) and create confusion that could jeopardize clinical services to individuals with APD. In our perspective article, we rebut Neijenhuis et al. (1), and more importantly, we present a rationale for evidence-based practice founded on the premise that research on APD is only clinically applicable when conducted on clinical populations diagnosed with APD.